STATISTICAL ANALYSIS OF INFANT MORTALITY RATE IN MIZORAM. - Vanlalhriatsaka; Mukesh Ranjan; Lalpawimawha; R. Zoramthanga; Lallawmsanga; Benjamin Roluahpuia (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Infant Mortality Rate (IMR) is the number of children who die before completing his or her first birthday day. It is usually taken as per 1000 live birth. According to census 2011, the population of Mizoram was 10.97 lakhs only and the study of Infant Death is very important for our future. Therefore, this paper is based on statistical analysis of infant mortality rate in Mizoram. In this paper, we use secondary data from “HEALTH AND FAMILY WELFARE DEPARTMENT” Government of Mizoram. In this paper, we apply time series trend for determine the trend and estimate the parameters. We also followed the trend to forecast for the next 10 years and the Quadratic Model is the best model to forecast. Based on our findings, we need more workshops or public awareness about maternal healthcare, so that we can alienate from Mizoram and we can make a better Mizoram for the future.